Maintaining the liver abscess suspect rate in pediatrics - Parada-Cabal, Ana Carolina (2023)
Hepatic abscess of pyogenic and amoebic etiology is a predominant pathology in adults. The incidence in pediatrics varies according to risk factors. In recent years, a decrease in its presentation has been evidenced, which potentially generates a loss of sensitivity for timely diagnosis, for which recall is required. The case of an eight-year-old male patient with a diagnosis of liver abscess is described and a review of the literature of the pathology in pediatric age, its etiology, classification, clinical manifestations, diagnosis and management is carried out in order to maintain the index of suspicion in the clinician.